2005
DOI: 10.1016/j.biopsych.2005.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Predictors of Attention-Deficit/Hyperactivity Disorder Persistence into Adulthood: Results from the National Comorbidity Survey Replication

Abstract: No modifiable risk factors were found for adult persistence of ADHD. Further research, ideally based on prospective general population samples, is needed to search for modifiable determinants of adult persistence of ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
330
2
17

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 560 publications
(376 citation statements)
references
References 62 publications
(50 reference statements)
27
330
2
17
Order By: Relevance
“…[1][2][3][4] Several follow-up studies have shown that at least 30% of ADHD patients diagnosed during childhood continue to suffer the disorder during adolescence and adulthood. [5][6][7][8] The etiology of ADHD is complex, with the involvement of both genetic and environmental factors. Twin, family and adoption studies, however, support the view that there is a major genetic component in its susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Several follow-up studies have shown that at least 30% of ADHD patients diagnosed during childhood continue to suffer the disorder during adolescence and adulthood. [5][6][7][8] The etiology of ADHD is complex, with the involvement of both genetic and environmental factors. Twin, family and adoption studies, however, support the view that there is a major genetic component in its susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…O TDAH está freqüentemente associado a comprometimentos acadêmico, social e profissional, além de haver maior incidência de transtornos psiquiátricos em portadores quando comparados à população geral, e os sintomas freqüentemente permanecem durante a vida adulta (Kessler et al, 2005). Para o diagnóstico, os sintomas devem gerar comprometimento significativo em pelo menos dois contextos diferentes, além de não serem mais bem explicados por outro transtorno mental.…”
Section: Introductionunclassified
“…Controlling for severity and excluding treatment, none of the other variables (sociodemographics, childhood adversity, traumatic life experiences and comorbidity) significantly predicted persistence, even though they were significantly associated with childhood ADHD [30]. Many studies reported adult persistence was much greater for inattention than for hyperactivity/impulsivity [6,30].…”
Section: Course and Prognosismentioning
confidence: 99%
“…When parent report is used, the prevalence increases to 46% [28]. The [30] study reported that 1 in 3 childhood ADHD still met DSM-IV criteria when aged 18-to 44-years [30]. In [32] study 40% of 18-to 20-year-old "grown up" ADHD patients met full criteria for ADHD, but 90% had at least five symptoms of ADHD [32].…”
Section: Epidemiologymentioning
confidence: 99%